Sosialisasi Penggunaan Aplikasi Fuzzy Mamdani Untuk Peningkatan Tata Kelola LPPM Universitas Graha Nusantara Padangsidimpuan - Alwendi, Alwendi; Samosir, Khairunnisa; Mandopa, Andi Saputa (Welfare : Jurnal Pengabdian Masyarakat, 2023)
The vision of higher education always leads to the dharma of higher education. One manifestation of the Tridharma of Higher Education is scientific work or conducting research. This socialization aims to map the needs of journal managers and improve journal governance, especially governance related to OJS journals at Graha Nusantara University Padangsidimpuan. The expected output is that journal managers will receive an overview, information, suggestions, and input related to OJS management from managed journals, such as costs for publishing an article. This socialization provides benefits and understanding regarding the financial governance of the journal, so that it can indirectly improve the quality and ranking of the journals that are managed. This socialization aims to improve the image and competitiveness of institutions by increasing the value of both study program accreditation and university accreditation.